The impact of co-branding on consumer purchase intentions in the automotive industry - Song, Jiazheng; Wei, Yuqian; Wang, Mingyang; Zhang, Yida (Journal of Asian Business Strategy, 2024)
This study aims to delve into the influence of co-branding on consumer purchase intentions in the automotive industry and the impact of brand image. It seeks to analyze how co-branding is carried out, its characteristics, and how it affects consumers’ brand perceptions and purchase decisions, especially exploring consumers’ acceptance and willingness to buy co-branded products. A quantitative research methodology is adopted, involving questionnaire design and data collection through an online survey. Multiple analyses, such as frequency, reliability, validity, factor, correlation, and regression analyses, are conducted to examine the data. Co-branding has a positive effect on consumer purchase intention. Brand fit, innovativeness, and product complementarity are crucial factors contributing to the success of co-branding. Brand image has a positive moderating impact, and complementary brand images enhance consumers’ purchase intention. The study also reveals that these factors can explain a significant portion of the variance in purchase intention. Automobile brands can enhance their attractiveness and market competitiveness by engaging in co-branding with suitable brands, focusing on brand fit, innovation, and product complementarity. Maintaining and enhancing a positive brand image is of great importance. Additionally, demographic information can help brands target consumers more effectively and design co-branding campaigns that better meet consumers’ needs and preferences. These findings offer practical guidance for marketers to utilize co-branding strategies more efficiently and boost brand value.